Testing Audit Quality and Corporate Governance Implementation on Financial Statement Integrity in Companies Listed on the Indonesian Sharia Stock Index (ISSI) - Rika Lidyah; Gibtiah Gibtiah; Oki Sania Riski (UNIVED Press, 2023)
This study aims to determine the effect of audit quality and corporate governance implementation on the integrity of financial statements in companies listed on ISSI in 2016-2018. This research is descriptive verification using quantitative methods. The population in this study were companies listed on ISSI in 2016-2018. The sample selection technique used purposive sampling and obtained 335 companies included with a period of 3 years so that 1005 samples were observed. The analysis method used in this observation is panel data regression using Eviews 9.0 software. The results showed that audit quality, institutional ownership, managerial ownership, audit committee and independent board of commissioners simultaneously affect the integrity of financial statements. Partially, audit quality, institutional ownership, audit committee and independent board of commissioners affect the integrity of financial statements while managerial ownership has no effect on the integrity of financial statements.